Monitoring Perkembangan Cabor Unggulan Jawa Tengah Dalam Persiapan PON XXI - Umam, Khotibul; Rumini, Rumini; Junaidi, Said (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The research aims to determine the development of Central Java's leading sports in preparation for PON XXI Aceh, North Sumatra. The research approach used is qualitative with a descriptive approach. This research uses primary data from research informants. Data sources were obtained from observations, interviews, and documentation from research informants. Credibility testing was carried out using the triangulation method of sources and data. The research results showed compliance in monitoring Central Java's leading sports branches towards PON XXI 2024 is good but still requires improved communication and integration. The monitoring system for Central Java's leading sports branches for PON XXI 2024 is running well with increasing performance and optimal readiness. Athletes from leading Central Java sports show positive progress, although their endurance and physical consistency still need improvement. Intensive training, health monitoring, and routine evaluations continue to be carried out to ensure optimal readiness of Central Java athletes towards PON XXI 2024. The research conclusion is that monitoring the development of Central Java's leading sports branches ahead of PON XXI Aceh-North Sumatra 2024 shows significant progress, with sound system implementation and routine evaluations that support athlete readiness. Keywords: Evaluation, Monitoring, Sport